Temperature-responsive solvation enabled by dipole-dipole interactions towards wide-temperature sodium-ion batteries - Meilong Wang; Luming Yin; Mengting Zheng; Xiaowei Liu; Chao Yang; Wenxi Hu; Jingjing Xie; Ruitao Sun; Jin Han; Ya You; Jun Lu (Nature Communications)
Abstract Rechargeable batteries with high durability over wide temperature is needed in aerospace and submarine fields. Unfortunately, Current battery technologies suffer from limited operating temperatures due to the rapid performance decay at extreme temperatures. A major challenge for wide-temperature electrolyte design lies in restricting the parasitic reactions at elevated temperatures while improving the reaction kinetics at low temperatures. Here, we demonstrate a temperature-adaptive electrolyte design by regulating the dipole-dipole interactions at various temperatures to simultaneously address the issues at both elevated and subzero temperatures. This approach prevents electrolyte degradation while endowing it with the ability to undergo adaptive changes as temperature varies. Such electrolyte favors to form solvation structure with high thermal stability with rising temperatures and transits to one that prevents salt precipitation at lower temperatures. This ensures stably within a wide temperature range of ‒60 −55 °C. This temperature-adaptive electrolyte opens an avenue for wide-temperature electrolyte design, highlighting the significance of dipole-dipole interactions in regulating solvation structures.